PENGARUH KEPEMIMPINAN VISIONER TERHADAP BUDAYA ORGANISASI DAN KOMITMEN SERTA IMPLIKASINYA PADA KINERJA APARATUR SIPIL NEGARA - Mustaking Mustaking; Arifuddin Arifuddin (AkMen JURNAL ILMIAH, 2023)
The purpose of this research is to analyze the extent of the influence of visionary leadership on organizational culture and organizational commitment, as well as its implications on the Performance of Civil Servants (ASN) at Terminal (A Study at the BPTD of Region XIX, South Sulawesi and West Sulawesi Provinces). To achieve this objective, data collection techniques such as interviews, questionnaires, literature review, and documentation were employed. The analysis methods used were descriptive analysis, data quality testing, classical assumption testing, hypothesis testing, and determination coefficient. The research findings indicate that visionary leadership has an influence on organizational culture, organizational commitment, and the performance of ASN. This suggests that effective implementation of visionary leadership by leaders can enhance organizational culture and organizational commitment, thus affecting the performance of ASN. Furthermore, the results of the conducted mediation test reveal that both organizational culture and organizational commitment can mediate the influence of visionary leadership on the performance of ASN at Terminal in the BPTD of Region XIX, South Sulawesi and West Sulawesi Provinces.